Interaction Among Government and Business: Analysis of Problems and Methods of Their Decision ("Journal "U". Economy. Management. Finance.", 2021)
The primary purpose of the real article is illumination of problems of cooperation of the state and business, and also consideration and analysis of problems and methods of their decision. Most essential from them is predominance of informal networks of management by conflicts. They develop rules on that business and state build the relations, compensating weak formal institutes the same. As between business and state it is possible to distinguish the row of acute angles, such as: absence of clear and unambiguous «rules of game», guarantees of institute of peculiar. Partnership between enterprises and states in Russia can be certain the leading role of the state.
Keywords: business; state; interaction; government; public-private partnership; interaction of government and business